Evaluation of antiretroviral use in children managed in public clinics of Mopani District, Limpopo Province : towards a dosing and dispensing training programme for nurses - Mabila, Linneth Nkateko (My University, 2022)
Antiretroviral (ARV) management in children is considered a challenging process, and patients receiving ARVs remain at risk of medication errors. Recently, there has also been a noticeable increase in Treatment Failure (TF) and the development of drug resistance amongst children on ART. However, ART failure amongst children seems to be an under-recognised issue, and adherence to treatment guidelines is reported to be a challenge among nurses caring for People Living with HIV (PLWHIV). Hence, the aim of this study was to explore the prescribing practices, and to determine the knowledge, understanding, and competence levels of NIMART-trained nurses’ in the management of children on Antiretroviral Therapy (ART) in Public Health Care (PHC) facilities located in a rural district of Limpopo Province. To attain the purpose of the study, the researcher in this study adopted a mixed-method, in an explanatory sequential manner. The quantitative phase adopted a descriptive cross-sectional and retrospective census of medical records to determine whether or not the children on ART were prescribed the correct ARV regimen, dose, strength, dosing frequency and received the correct quantities to last until the next appointment date. Whereas the qualitative phase embraced a total purposive sampling of the NIMART-trained professional nurses to explore their knowledge, understanding and views of ART management in children. The results highlighted that these children under study even though they were prescribed a correct ARV regimen in (n=7045; 96%) of the cases;they were only correctly dosed in (n=7797; 53%); and prescribed the correct strength (n=9539; 77%), with only (n=2748; 36.9%) having received the correct quantity of treatment to last them until the next appointment date. Most nurses even though they rated themselves very knowledgeable and competent in paediatric HIV/AIDS management. This finding was contradicting the results obtained from the medical records, as well as their responses to the given case scenario depicted some level of non-adherence to treatment guidelines as well as a lack of understanding of ARV management. From the findings of this ARV utilisation review and the implementation of the developed ART dosing and dispensing training programme. The study concludes that the nurse's prescribing practice was irrational in this cohort of children, and most prescriptions did not entirely comply with the 2014/15 HIV/AIDs treatment recommendations. Since, this cohort of children was found to be susceptible to medication related errors such as; Drug omissions in ARV regimens; Incorrect dosing & dosing frequencies; as well as incorrectly supplied quantities. From the study findings it is recommended that ARV stewardship programs should be considered in order to develop and establish a core strategy for enhancing quality improvement in the management of HIV-infected children on ART in resource-limited settings, not only to inundate viral suppression and maintain it, but also to help achieve the UNAIDS 95- 95-95 target in children under 15 year
Thesis (Ph.D. (Pharmacy)) -- University of Limpopo, 2022
Keywords: Prescribing Practices; Children; Antiretroviral Therapy; Virally Unsuppressed; Primary Health Care; Underdose; Overdose; Antiretroviral agents; Highly active antiretroviral therapy; Drugs -- Prescribing; Drugs -- Overdose; Medication errors